Mycoplasma bovis pneumonia in feedlot cattle and dairy calves in Argentina - Margineda, Carlos Augusto (2017)
Mycoplasma bovis has emerged as an important cause of feedlot pneumonia in many countries. The aim of this paper is to describe six cases of bovine Mycoplasma pneumonia in five different premises in Argentina. Gross examination revealed chronic bronchopneumonia with multiple foci of caseous necrosis. Microscopically, these contained a necrotic center with abundant hypereosinophilic granular material surrounded by granulation tissue. Affected lung tested positive for M. bovis by immunohistochemistry and electron microscopy revealed membranous structures compatible with Mycoplasma spp. To our knowledge, this is the first report of M. bovis pneumonia in Argentina.